Sovereign wealth funds in central and eastern Europe: Scope and methods of financial penetration - Piotr Wiśniewski; Tomasz Kamiński; Marcin Obroniecki (e-Finanse: Financial Internet Quarterly, 2015)
The Central and Eastern European (CEE) capital markets (of Poland, Lithuania, Latvia, Estonia, the Czech Republic, Slovakia, Hungary, Ukraine and, to a limited extent, Belarus) are gradually evolving towards increased breadth (diversity) and depth (liquidity), however, they are still exposed to considerable cross-country volatility and interdependence spill-overs - especially in times of capital flight to more established asset classes ("safe havens"). Sovereign Wealth Funds (SWFs) have widely been censured for their undesirable political interference and chronic operational opacity. This paper demonstrates that in CEE, contrary to widespread perceptions attributable to developed markets, SWFs can act as natural and powerful risk mitigators (contributing to a more stable capital base and reduced systemic volatility). Such a proposition is premised on several factors specific to SWFs oriented to CEE. They comprise: strategic long-termism and patience in overcoming interim pricing deficiencies, commitments to elements of a broadly interpreted infrastructure, and absence of overt conflicts of interest with the CEE host economies. The paper, besides reviewing the utilitarianism of SWFs in the CEE's risk mitigation context, highlights regulatory and technical barriers to more SWF funding for CEE. It also recommends policy measures to the CEE economies aimed at luring more host-friendly SWF investment into the region.
Keywords: G23; G24; G28; F30; 330; sovereign wealth funds; SWFs; risk mitigation; stability of financial industries; political impact